SOSIALISASI PENGGUNAAN PUPUK KASCING PADA TANAH ULTISOL UNTUK PERTUMBUHAN BIBIT KAKAO - Ida Nursanti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2023)
Ultisol soil has poor physical and chemical soil characteristics in supporting plant growth. So that the use of ultisol soil can be optimized as a medium for planting cocoa seeds, you can use organic fertilizer, including vermicompost. Vermicompost fertilizer can improve the physical and chemical properties of soil, increase soil fertility, and increase the productivity of ultisol soil. The aim of this outreach is to utilize vermicompost fertilizer to support the growth of cocoa plants on ultisol soil, and to promote the procurement of cocoa seeds, especially in Solok Village. The results of previous research show that applying various doses of vermicompost fertilizer to ultisol soil has an influence on shoot dry weight and cocoa plant quality index, plant height, stem diameter and root dry weight.